E-zasoby do kształcenia zawodowego - wyzwanie dla cyfrowych kompetencji nauczycieli = E-resources for vocational education - a challenge for teachers` digital competences - Solecka, Bożena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article is an attempt to introduce the readers to issues related to the need for developing digital competences of vocational education teachers in relation to the systemic development of e-resources dedicated to this area of education. The considerations are based on an analysis of digital competence of teachers in the field of subject-specific and methodological competences in the context of changing requirements indicated in the Core Curriculum for Vocational Education. The author also aims to draw attention to the issue of emerging tools embedded in a virtual environment, which are available to teachers and students of vocational education through the Integrated Educational Platform (ZPE).
Keywords: digital competences of teachers; vocational education; educational platform; e-materials; e-resources; cyfrowe kompetencje nauczycieli; kształcenie zawodowe; platforma edukacyjna; e-materiały; e-zasoby